# Solve for m -2/3m=6

-23m=6
Multiply both sides of the equation by -32.
-32⋅(-23)⋅m=-32⋅6
Simplify both sides of the equation.
Simplify -32⋅(-23)⋅m.
Cancel the common factor of 3.
Move the leading negative in -32 into the numerator.
-32⋅(-23)⋅m=-32⋅6
Move the leading negative in -23 into the numerator.
-32⋅-23⋅m=-32⋅6
Factor 3 out of -3.
3(-1)2⋅-23⋅m=-32⋅6
Cancel the common factor.
3⋅-12⋅-23⋅m=-32⋅6
Rewrite the expression.
-12⋅-2⋅m=-32⋅6
-12⋅-2⋅m=-32⋅6
Cancel the common factor of 2.
Factor 2 out of -2.
-12⋅(2(-1))⋅m=-32⋅6
Cancel the common factor.
-12⋅(2⋅-1)⋅m=-32⋅6
Rewrite the expression.
-1⋅-1⋅m=-32⋅6
-1⋅-1⋅m=-32⋅6
Multiply.
Multiply -1 by -1.
1⋅m=-32⋅6
Multiply m by 1.
m=-32⋅6
m=-32⋅6
m=-32⋅6
Simplify -32⋅6.
Cancel the common factor of 2.
Move the leading negative in -32 into the numerator.
m=-32⋅6
Factor 2 out of 6.
m=-32⋅(2(3))
Cancel the common factor.
m=-32⋅(2⋅3)
Rewrite the expression.
m=-3⋅3
m=-3⋅3
Multiply -3 by 3.
m=-9
m=-9
m=-9
Solve for m -2/3m=6

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top